Analisis Perilaku Seismik Struktur Beton Bertulang dengan Sistem Base Isolation HDRB pada Gedung 6 Lantai di Surabaya - Saputra, Mohamad Dicky; Sutriono, Bantot (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesia is a region with high seismic activity, including Surabaya, which is influenced by the Kendeng Fault. This study aims to analyze the effect of using High Damping Rubber Bearing (HDRB) on the seismic performance of a six-story office building. The analysis was carried out using ETABS based on SNI 1726:2019 by comparing a fixed-base structure and an HDRB-isolated structure. The parameters evaluated include natural period, base shear, interstory drift, and P-Delta effects. The results show that HDRB increases the natural period and significantly reduces base shear and interstory drift. Therefore, HDRB is effective in improving seismic performance and can be considered as an alternative design for buildings in moderate seismic hazard areas.